Admission fibrinolytic profile predicts clot lysis resistance in stroke patients treated with tissue plasminogen activator - Ribo, Marc; Montaner, Joan; Molina, Carlos A.; Arenillas, Juan F.; Santamarina, Esteban; Alvarez-Sabín, José (Thrombosis and Haemostasis, 2004)
Endogenous fibrinolysis inhibitors may be involved in t-PA resistance, decreasing stroke thrombolysis beneficts. We aim to determine the impact of pretreatment levels of plasminogen activator inhibitor (PAI-1), lipoprotein(a), thrombin-activatable fibrinolysis inhibitor (TAFI) and homocysteine on arterial recanalization and outcome. Forty-four consecutive patients with acute proximal middle cerebral artery occlusion were studied, including assessment of transcraneal Doppler artery patency. The neurological status was determined by NIH Stroke Scale (NIHSS) and long-term outcome with modified Rankin Scale (mRS). Patients who recanalized after t-PA infusion had lower PAI-1 levels than those who remained occluded. Similarly, patients who achieved dramatic clinical recovery at 12 hours exhibited significantly lower PAI-1 levels as those independent (mRS≤2) at third month. We observed a trend towards lower lipoprotein p(a) in patients who achieved recanalization at 1 hour, whereas no relation was found between TAFI or homocysteine levels and recanalization. After a regression model was applied the only independent predictor of thrombolysis resistance was baseline PAI-1≤34 ng/ml, such that high PAI-1 levels interfere with tPA-induced recanalization in stroke, predicting a higher susceptibility towards clot-lysis resistance and poor outcome.
Keywords: Cerebrovascular disease; clinical trials; fibrinolytic therapy; fibrinolysis inhibitors; thrombin activatable fibrinolysis inhibitor / carboxypeptidases; ultrasound / diagnosis